1994
DOI: 10.1093/treephys/14.7-8-9.769
|View full text |Cite
|
Sign up to set email alerts
|

Effects of elevated CO2 on growth and chloroplast proteins in Prunus avium

Abstract: To predict the future carbon sequestering capacity of trees, we need information about the possible acclimatory mechanisms of plant growth and photosynthesis in rising atmospheric CO(2) under a variety of environmental conditions. We have, therefore, studied the growth response of a tree species (Prunus avium L. Stella (wild cherry)) to elevated CO(2) and characterized the associated changes in photosynthetic machinery of the leaf tissue. Self-pollinated seedlings and mature cuttings (clones) from the same par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 20 publications
2
25
0
Order By: Relevance
“…This is in accordance with previous studies carried out under elevated CO 2 [47][48][49][50]. Plants lose the ability to take up soil nitrate (most common form of nitrogen) and convert it into organic compounds such as proteins at enriched CO 2 conditions.…”
Section: Discussionsupporting
confidence: 92%
“…This is in accordance with previous studies carried out under elevated CO 2 [47][48][49][50]. Plants lose the ability to take up soil nitrate (most common form of nitrogen) and convert it into organic compounds such as proteins at enriched CO 2 conditions.…”
Section: Discussionsupporting
confidence: 92%
“…Prunus avium -2.51 Wilkins (1994) 0.09 Centritto (1999) 0.21 Kerstiens (1994) Quercus petrea -1.36 Guehl (1994) …”
Section: Uv-bmentioning
confidence: 99%
“…Several explanations have been proposed for photosynthetic acclimation to elevated CO 2 , including a reduction in the activity of sinks for carbohydrate, and as a consequence a source-sink imbalance (Thomas and Strain 1991;Long and Drake 1992). Under elevated CO 2 , when photosynthesis greatly exceeds the capacity for photosynthate utilization, it has been shown that sugars accumulate and modulate the transcription of chloroplast proteins Willkins et al 1994). In the present study, the increase in the pool of total soluble sugars and starch in leaves of plants grown at elevated CO 2 suggests the down-regulation of photosynthesis in plants grown at elevated CO 2 .…”
Section: Discussionmentioning
confidence: 99%